Opinions of Administrators, Teachers, and Parents on the Evaluation of the Effectiveness of the Addiction Programs Implemented in Secondary Schools - Aktan, Osman; Yılmaz, Metin; Yılmaz, Merve (Addicta: The Turkish Journal on Addictions, 2018)
This study aims to use the opinions of administrators, teachers, and parents to evaluate the effectiveness of an addiction prevention educational program devised for and presented middle school students. A case study was used in the analysis of the data collected. The study group consisted of 156 individuals, including 12 administrators, 128 teachers, and 16 parents. Semi-structured interview forms were used to collect qualitative data. Validity and reliability were assessed through a pilot study. A content analysis was conducted to analyze qualitative data. The findings, revealed that the addiction prevention program was effective in raising participants’ awareness about addiction prevention and in increasing their knowledge about substance addiction, technology addiction, and other harmful habits. Teachers, administrators, and parents emphasized that the problem of the addiction prevention educational program was mainly lack of practical activities, lack of adequate support for parent, inadequate time allotted for teaching hours for the students, and lack of activities for implementation. The results suggest that it would be beneficial to organize addiction prevention educational programs in terms of content, implementation, timing, and support for parents, includes practical field studies.Citation: Aktan, O., Yılmaz, M., & Yılmaz, M. (2018). Opinions of administrators, teachers, and parents on the evaluation of the effectiveness of the addiction programs implemented in secondary schools. Addicta: The Turkish Journal on Addictions, 5, 637−664. http://dx.doi.org/10.15805/addicta.2018.5.4.0041
Keywords: Middle school; Student; Addiction; Addiction Prevention Program; Program evaluation